A first course in database systems - Ullman, Jefferey D. (Prenticice Hall, 2008)
Written by well-known computer scientists, this accessible and succinct introduction to database systems focuses on database design and use. It provides in-depth coverage of databases from the point of view of the database designer, user, and application programmer. The authors provide an overview of important programming systems (e.g., SQL, JDBC, PSM, CLI, PHP, XQuery, etc.) and the intellectual framework to put them into context. For software engineers, database engineers, and programmers.